State, Society, and University: Historical Context of Chinese Higher Education - Rungfamai, Kreangchai (SUSURGALUR, 2014)
ABSTRACT: In many cases, ideally, the Society assumes that the State can operate on behalf of the Society by intervening Universitiesâ activities in order to meet societal expectations. Conversely, the Society can also pressure the State via the University behaving as a buffer zone of interests between the State and the Society. This paper is intended to reflect the intertwined role and interconnected relationship between State, Society, and University in China. It highlights how these three main stakeholders have responded to their environments by emphasizing the role of Universities. The paper provides a general overview of the role of higher education in the Chinese society, and its responses towards other stakeholders and changes in its environments from the past to the present. From the perspective of chronological history, the analysis of the evolution of Chinese higher education is based upon the premise that these three main stakeholders: State, Society, and University, embedding in their own socio-cultural underpinning factors have to respond to changing environments. The role of Universities is substantially highlighted as the key stakeholder in this paper. KEY WORD: State, university, society, historical context, Chinese higher education, stakeholders, and changing environments.IKHTISAR: âNegara, Masyarakat, dan Universitas: Konteks Sejarah tentang Pendidikan Tinggi Cinaâ. Dalam banyak kasus, idealnya, Masyarakat berasumsi bahwa Negara dapat beroperasi atas nama Masyarakat dengan intervensi kegiatan Universitas dalam rangka memenuhi harapan Masyarakat. Sebaliknya, Masyarakat juga dapat menekan Negara melalui kegiatan Universitas sebagai zona penyangga kepentingan antara Negara dan Masyarakat. Tulisan ini dimaksudkan untuk merefleksikan jalinan peran dan hubungan yang saling berkaitan antara Negara, Masyarakat, dan Universitas di Cina. Ini menyoroti bagaimana tiga pengampu kepentingan utama ini telah merespon lingkungan mereka dengan menekankan peran Universitas. Makalah ini memberikan gambaran umum tentang peran pendidikan tinggi dalam masyarakat Cina, dan tanggapan terhadap pengampu kepentingan lainnya dan perubahan lingkungan dari masa lalu hingga saat ini. Dari perspektif sejarah kronologis, analisis evolusi pendidikan tinggi Cina didasarkan pada premis bahwa tiga pengampu kepentingan utama ini: Negara, Masyarakat, dan Universitas, harus melekat dalam sosial-budaya mereka sendiri sebagai faktor-faktor pendukung dan merespon perubahan lingkungan. Peran perguruan tinggi secara substansial disorot sebagai pengampu kepentingan utama dalam makalah ini.KATA KUNCI: Negara, universitas, masyarakat, konteks historis, pendidikan tinggi Cina, pengampu kepentingan, dan perubahan lingkungan.About the Author: Kreangchai Rungfamai, Ph.D. is Freelance Researcher of the Thailand. He has earned Ph.D. from the Faculty of Education, the University of Hong Kong, Hong Kong (China). His e-mail address is: kreangchai_tdai@hotmail.comHow to cite this article? Rungfamai, Kreangchai. (2014). âState, Society, and University: Historical Context of Chinese Higher Educationâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(2), September, pp.207-216. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808.Â Chronicle of the article: Accepted (May 29, 2014); Revised (August 12, 2014); and Published (September 24, 2014).